Iceland : Second Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report ;, 2012)
The report throws light on the process of recovery from the global financial crisis in Iceland. The strong growth performance witnessed in 2011 seems to continue in 2012. The closing output gap and the decline in unemployment have been marked as positive changes. The major external and internal risks to the financial sector are highlighted, and emphasis is laid on the need to address risks and achieve fiscal targets by maintaining a strong, independent, and adequately resourced Financial Supervisory Authority (FME).